2019
DOI: 10.1093/mnras/stz2355
|View full text |Cite
|
Sign up to set email alerts
|

Not so different after all: properties and spatial structure of column density peaks in the pipe and Orion A clouds

Abstract: We present a comparative study of the physical properties and the spatial distribution of column density peaks in two Giant Molecular Clouds (GMC), the Pipe Nebula and Orion A, which exemplify opposite cases of star cluster formation stages. The density peaks were extracted from dust extinction maps constructed from Herschel/SPIRE farinfrared images. We compare the distribution functions for dust temperature, mass, equivalent radius and mean volume density of peaks in both clouds, and made a more fair comparis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 66 publications
6
9
0
Order By: Relevance
“…3). This value is very consistent with the values obtained for the linear regime of the MSDC in the Pipe Nebula (-0.68) and the Lupus I cloud (-0.72) (Román-Zúñiga et al 2019), where this linear regime is found at similar or slightly larger spatial scales of 2000 -8000 AU. The Y-axis is the number of companions, and the X-axis is angular separations.…”
Section: Typical Separations Between Fragmentssupporting
confidence: 91%
See 1 more Smart Citation
“…3). This value is very consistent with the values obtained for the linear regime of the MSDC in the Pipe Nebula (-0.68) and the Lupus I cloud (-0.72) (Román-Zúñiga et al 2019), where this linear regime is found at similar or slightly larger spatial scales of 2000 -8000 AU. The Y-axis is the number of companions, and the X-axis is angular separations.…”
Section: Typical Separations Between Fragmentssupporting
confidence: 91%
“…The clustering regime is associated with the fragmentation of the cloud, while the binary regime is affected by additional processes such as the dynamical interactions between the different members of a multiple system. The value of the slope found here for W51 North (SE1), -0.8±0.1 (Section 4.1), is fully consistent with the expected value for the clustering regime in other clouds of the Milky Way such as Taurus, Ophiucus, the Pipe Nebula, Lupus I, or OMC-1S (Gómez et al 1993;Simon 1997;Palau et al 2018;Román-Zúñiga et al 2019) and clearly shallower than the typical value of the binary regime. Although W51 North is very young and part of the fragments identified here could merge with time, the fact that the slope of the MSDC plot for W51 North precisely corresponds to the expected value for the clustering regime suggests that a protocluster is in the making in W51 North.…”
Section: A Cluster-like Spatial Distribution Of Fragments Insupporting
confidence: 88%
“…It is interesting to note that in a study of the integral shape filament in Orion, Kainulainen et al (2017) found that significant grouping of dense cores is found below scales of 17000 au (see also Román-Zúñiga et al 2019), similar to what we find Fig. 5.…”
Section: Fragmentation and Continuum Emissionsupporting
confidence: 87%
“…It is interesting to note that in a study of the integral shape filament in Orion, Kainulainen et al (2017) found that significant grouping of dense cores is found below scales of 17000 au (see also Román-Zúñiga et al 2019), similar to what we find in Fig. 5.…”
Section: Fragmentation and Continuum Emissionsupporting
confidence: 87%